2009
DOI: 10.1017/s0025100308003605
|View full text |Cite
|
Sign up to set email alerts
|

Luanyjang Dinka

Abstract: Dinka is a Western Nilotic language within the Nilo-Saharan family. There are over two million speakers (Gordon 2005). The Dinkas live along the banks of the White Nile and its tributaries in Southern Sudan. There are also communities elsewhere within Sudan, in particular in the capital Khartoum, and abroad. Cows play a key role in the Dinka economy, and also in the sociocultural system. Four major dialect areas are commonly distinguished: Padang, Rek, Agar, and Bor. The variety of Dinka represented here – Lua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…A salient characteristic of Dinka phonology is its rich system of suprasegmental contrasts: tone, vowel length, and voice quality are all distinctive, independently of one another (Andersen 1987, Remijsen & Manyang 2009). The minimal set in 2 illustrates the vowel-length contrast.…”
Section: 2mentioning
confidence: 99%
“…A salient characteristic of Dinka phonology is its rich system of suprasegmental contrasts: tone, vowel length, and voice quality are all distinctive, independently of one another (Andersen 1987, Remijsen & Manyang 2009). The minimal set in 2 illustrates the vowel-length contrast.…”
Section: 2mentioning
confidence: 99%
“…Alternations between short (/V/) and long (/VVV/) in this context were coded as involving a single degree of vowel length. For further detail on vowel length before coda /r/ see Remijsen & Gilley 2008, Remijsen & Manyang 2009 Note that in the first instance we are concerned only with DIFFERENCES between singular and plural; we make no assumption about which form is unmarked and which is marked, because of the general nature of Nilo-Saharan number morphology noted earlier. That is, our coding is neutral with regard to the direction of the difference, and, for example, a difference in vowel length between short /V/ and medium /VV/ is coded as a difference of one degree of vowel length regardless of which vowel length occurs in the singular form and which in the plural.…”
Section: Degrees or Typesmentioning
confidence: 99%
“…Consequently we took great care to be sure that the forms we report are correct, putting words in different sentence contexts and carrying out instrumental acoustic measurements where necessary, and we are confident that the data can be considered reliable. As noted above, the dialect under study is Luanyjang Dinka, the sound system of which is familiar to us from several studies carried out in conjunction with the work reported here (Remijsen & Gilley 2008, Remijsen & Ladd 2008, Remijsen & Manyang 2009). The data are based on the speech of the third author, but have been checked for consistency with other speakers in Khartoum; for only ten nouns out of the 400 was there any variability.…”
mentioning
confidence: 96%
See 2 more Smart Citations